Entre o western e o nordestern : os possíveis diálogos de Lima Barreto e Glauber Rocha no cinema cangaço (O cangaceiro 1953, Deus e o diabo na terra do sol 1964 e O dragão da maldade contra o santo guerreiro 1969) - Neves, Anderson Rodrigues (2013)
Dwell in the relationship between History and Cinema in order to understand the construction of historical narrative about Brazilian cinema. Study, understand and discuss the relationships and possible dialogue between the films O Cangaceiro of Lima Barreto, Deus e o Diabo na Terra do Sol and O Dragão da Maldade contra o Santo Guerreiro both of Glauber Rocha. The development of our analysis is the convergence of gender and aesthetics adopted by the directors, even though the first makes clear the choice of the western states and the second to build a Brazilian aesthetic, the aesthetic of hunger. So, we do the opposite movement of the authors who point to the ranking of Brazilian cinema, electing the Cinema Novo as the benchmark for quality and innovation aesthetic-ideological.